A decade of nutrition research in Africa: assessment of the evidence base and academic collaboration. Issue 10 (7th October 2014) - Lachat, Carl; Roberfroid, Dominique; Van den Broeck, Lien; Van den Briel, Natalie; Nago, Eunice; Kruger, Annamarie; Holdsworth, Michelle; Garimoi Orach, Christopher; Kolsteren, Patrick
Abstract: Objective: Malnutrition in Africa has not improved compared with other regions in the world. Investment in the build-up of a strong African research workforce is essential to provide contextual solutions to the nutritional problems of Africa. To orientate this process, we reviewed nutrition research carried out in Africa and published during the last decade. Design: We assessed nutrition research from Africa published between 2000 and 2010 from MEDLINE and EMBASE and analysed the study design and type of intervention for studies indexed with major MeSH terms for vitamin A deficiency, protein–energy malnutrition, obesity, breast-feeding, nutritional status and food security. Affiliations of first authors were visualised as a network and power of affiliations was assessed using centrality metrics. Setting: Africa. Subjects: Africans, all age groups. Results: Most research on the topics was conducted in Southern (36 %) and Western Africa (34 %). The intervention studies (9 %; n 95) mainly tested technological and curative approaches to the nutritional problems. Only for papers on protein–energy malnutrition and obesity did lead authorship from Africa exceed that from non-African affiliations. The 10 % most powerfully connected affiliations were situated mainly outside Africa for publications on vitamin A deficiency, breast-feeding, nutritional status and food security. Conclusions: The development of the evidence base for nutrition research in Africa is focused on treatment and the potential for cross-African networks to publish nutrition research from Africa remains grossly underutilised. Efforts to build capacity for effective nutrition action in Africa will require forging a true academic partnership between African and non-African research institutions.